2018
DOI: 10.1039/c8cp00846a
|View full text |Cite
|
Sign up to set email alerts
|

Cyano-tryptophans as dual infrared and fluorescence spectroscopic labels to assess structural dynamics in proteins

Abstract: The steady state and time-resolved fluorescence and infrared (IR) properties of 4- and 5-cyanotryptophan (CNTrp) are investigated and compared, and the tryptophan (Trp) analogs are found to be very attractive to study structural and dynamic properties of proteins. The position of the nitrile substitution as well as the solvent environment influences the spectroscopic properties (solvatochromism). Similar to native Trp, electronic (nanosecond) lifetime and emission spectra are modulated by the environment, maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 50 publications
5
21
0
Order By: Relevance
“…To corroborate this notion, we examine the dependence of the C≡N stretching vibrational frequency (ν CN ) of 4CNI-NS on a solvent. Our results show that ν CN is sensitive to a solvent, similar to that observed for 4-cyanotryptohan (4CN-Trp) [13]. Therefore, this finding supports the idea that 4CNI-NS can be utilized to provide information about the local hydration and electrostatic environment of DNA in a site-specific manner.…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…To corroborate this notion, we examine the dependence of the C≡N stretching vibrational frequency (ν CN ) of 4CNI-NS on a solvent. Our results show that ν CN is sensitive to a solvent, similar to that observed for 4-cyanotryptohan (4CN-Trp) [13]. Therefore, this finding supports the idea that 4CNI-NS can be utilized to provide information about the local hydration and electrostatic environment of DNA in a site-specific manner.…”
Section: Introductionsupporting
confidence: 85%
“…More recently, Passow and Harki [10] have shown that 4CNI-NS can also be used as a universal DNA base. As demonstrated in previous studies [11,12,13], in comparison to indole and other indole derivatives, 4-cyanoindole (4CNI) (Figure 1) is significantly more fluorescent, has a long fluorescence lifetime, a red-shifted absorption spectrum, and an emission spectrum in the blue region of the visible spectrum. These qualities give 4CNI-NS a distinct advantage over 5NI-NS as it can serve as a fluorescence reporter.…”
Section: Introductionsupporting
confidence: 58%
“…A special class of indole derivatives, the cyanotryptophans are used as dual infrared and fluorescence spectroscopic labels to assess structural dynamics in proteins. 14 Markiewicz et al have shown that 5-cyanotryptophan fluorescence can be utilized as a sensitive probe of protein hydration. 15 The fluorescence lifetime of the different cyanoindoles in solution has been found to depend considerably on the solvent.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several methods for syntheses of 4CN-Trp or its derivatives have been reported in the literature (Figure 1, Table S1, ESI †). 13,[17][18][19][20][21] For example, Bartoccini et al 20 described the synthesis of N-acetyl-4CN-Trp methyl ester from 4-pinacol boronated ester 1. However, the product was a racemic mixture and the yield was low.…”
mentioning
confidence: 99%
“…Recently, another racemic synthesis of N-acetyl-4CN-Trp from 4-cyanoindole 2 was reported. 21 Since the experimental details were not described in that study, we attempted to reproduce its result by implementation of similar reaction conditions [22][23][24] known for tryptophan analogues but the desired product was obtained in very low yield in our hands. In the study of Hilaire et al, a short synthetic route to produce 4CN-Trp methyl ester from 4-bromo-L-tryptophan 3 in optically pure form was described.…”
mentioning
confidence: 99%